Strongly Almost Lacunary -Convergent Sequences - Adem Kılıçman; Stuti Borgohain (Abstract and Applied Analysis)
We study some new strongly almost lacunary -convergent generalized difference sequence spaces defined by an Orlicz function. We give also some inclusion relations related to these sequence spaces.